The concept of a multilevel model of ukraine's capacity as a place of medical tourism: development factors and prospects - Baiev, Vadim; Bakhov, Ivan; Bezpala, Olha; Veres, Kateryna; Mirzodaeva, Tetiana (My University, 2021)
In the age of globalized medicine, medical tourism is gaining an important global perspective on health. The global medical tourism market is also following this trend; according to forecasts by Grand View Research, Inc., the size of the global medical tourism market is expected to reach $179.6 billion by 2026. Medical tourism brings direct foreign currency income and contributes to the overall development of any economy. It ensures not only the creation of new jobs, but also the growth of associated enterprises such as those in the business of pharmaceuticals, medicines and tourism.

В епоху глобалізації медицини медичний туризм набуває важливого глобального погляду на здоров’я. Світовий ринок медичного туризму також слідує цій тенденції; згідно з прогнозами Grand View Research, Inc., очікується, що до 2026 року розмір світового ринку медичного туризму досягне 179,6 мільярдів доларів США. Медичний туризм приносить прямі доходи в іноземній валюті та сприяє загальному розвитку будь-якої економіки. Це забезпечує не тільки створення нових робочих місць, але й зростання асоційованих підприємств, таких як фармацевтичні, медичні та туристичні.
Keywords: tourism; medical tourism; model of medical tourism; country's capacity in the field of tourism; кафедра туристичного та готельного бізнесу; туризм; медичний туризм; модель медичного туризму; культурний потенціал у сфері туризму